Histologic effects of high intensity pulsed ultrasound exposure with subharmonic emission in rabbit brain in vivo - Vykhodtseva, N. I.; Damianou, Christakis A.; Hynynen, K. (My University, 1995)
In this study, the threshold for subharmonic emission during in vivo sonication of rabbit brain was investigated. In addition, the histologic effects of pulsed sonication above this threshold were studied. Two spherically curved focused ultrasound transducers with a diameter of 80 mm and a radius of curvature of 70 mm were used in the sonications. The operating frequencies of the transducers were 0.936 and 1.72 MHz. The sonication duration was varied between 0.001 and 1 s and the repetition frequency between 0.1 and 5 Hz. The threshold for subharmonic emission at the frequency of 0.936 MHz was found to be approximately 2000 W cm-2 and 3600 W cm-2 for pulse durations of 1 s and 0.001 s, respectively. The threshold was approximately 1.5-fold as high at a frequency of 1.72 MHz. However, there was considerable variation from experiment to experiment. The multiple pulse experiments at a frequency of 1.72 MHz and an intensity of 7000 W cm-2 showed that the histologic effects ranged from no observable damage of the tissue, to blood-brain barrier breakage, to local haemorrhagia, to local destruction of the tissue, to gross hemorrhage resulting in the death of the animal. The severity of the tissue damage increased as the pulse duration, number of pulses and their repetition frequency increased. The results indicate that the end point of the tissue damage may be controlled by selecting the sonication parameters. Such control over tissue effects can have several different applications when brain disorders are treated. © 1995.
Keywords: Bioeffects; Cavitation; Minimally invasive surgery; Ultrasound